Upcycling the barbeque grease into carbon nanomaterials. (January 2022) - Chan, K.F.; Ranade, A.K.; Desai, P.; Hazan, M.A.; Azman, N.F.I.; Shaharifin, S.; Kalita, G.; Mamat, M.S.; Tanemura, M.; Yaakob, Y.
Abstract: Carbon nanomaterials (CNMs) have been a remarkable material and impacted today's technology in various fields, such as enhancing agents for host material and environment-related applications. Green synthesis of CNMs gains attention as it requires low cost and less energy during the fabrications. In addition, the starting material is either environmental-friendly or a waste carbon compound that can be obtained from the household or catering industry. In this research, CNMs such as carbon nanotubes (CNTs) and graphitic carbon layers were synthesised using barbeque grease as carbon precursor via the chemical vapour deposition technique (CVD). The oil waste was analysed with gas chromatograph-mass spectrometry (GC–MS), and it showed that the oil waste contained a high amount of hydrocarbon chain such as pentadecane and 1-nonadecene, which decomposed into simple hydrocarbon bonding during the deposition and grew CNMs on the catalyst. SEM and TEM results showed that the CNTs with a diameter range of 42 ± 17 nm (outer) and 3.5 ± 0.5 nm (inner) were synthesised using the Ni catalyst. Raman and SEM revealed that the graphitic carbon layers with a D to G peak intensity ratio (ID /IG ) is 0.9898 were fabricated using Cu foil as the substrate. This research aims to discover novel and low-cost carbon precursors for the CVD system, to produce high-quality CNMs.